Pemilihan Paket Wisata One Day Tour Menggunakan Model Pendukung Keputusan TOPSIS - Yerik Afrianto Singgalen (Universitas Budi Darma, 2023)
The development of Labuan Bajo tourism attracts foreign and domestic tourists to explore various natural beauties through fun activities. Tour agents provide a variety of interesting activities and tourist visits to the islands around Labuan Bajo that can provide new experiences for tourists. The activities are sold through One-day tour packages in Labuan Bajo. Still, depending on the service provider, the itinerary description, admission ticket,Â and order of visit to the destination are very complicated. Considering this, this study uses the TOPSIS decision model in choosing One Day Tour tour packages in Labuan Bajo by considering the criteria of price, destination, duration, admission ticket, and service rating. Based on the results of this study, it can be seen that the highest preference value from the ranking results is the Full Day Trip to Explore 6 Destinations in Labuan Bajo and Komodo tour package, with a value of 0.673056111. Furthermore, the tour package that occupies the second position from the ranking results is the 1-day Komodo island Tour hopping around by Speed Boat with a preference value of 0.628303746. Meanwhile, the tour package that occupies the third position from the ranking results is One day Komodo trip with Bintang Komodo Tours with aÂ preference value of 0.53181476. This shows that the TOPSIS method produces recommendations for One Day Tour packages in Labuan Bajo for tourists by considering the price of tour packages, the number of destinations visited, the length of time or duration of tourist time, admission tickets in tour packages, and ratings The services of the travelers were previously related to the tour package. Thus, the selection of TOPSIS-based One Day Tour tour packages can minimize the risk that causes misunderstandings or tourist dissatisfaction related to the tour packages prepared by each travel agent.